Outdated Assessments from a University Teaching Perspective - Robles Barrantes, Andrés Ariel (2019)
Academic assessments have always been used by universities to gauge student learning. Yet, they have remained unchanged through time. The objective of this essay is to take a snapshot of current teaching and assessment practices. It is the essence of today´s university teaching staff to go far and beyond their traditional duty and continuously challenging their students to seek learning experiences outside of the classroom. Concepts taught by professors and lecturers should not only be based on market regulations and economic guidelines. They have the duty to focus on the individual and promote critical thinking in a world that is less creative and thought-driven and more focused on replication of knowledge, simultaneous repetition, rote memorization of information and frivolous numerical measurements.